Поняття санкції у теорії права - Сопронюк, О.; Soproniuk, А. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті встановлено етимологічне значення поняття«санкція»; проаналізовано теоретичні підходи до визначення санкції норми права; виокремлено суттєві ознаки, які його характеризують; піддано критиці концепцію позитивної відповідальності та санкцій-заохочень; встановлено інформаційний та превентивний ефекти існування та застосування санкцій до правопорушників; з’ясовано співвідношення та зв’язок між санкцією норми права та юридичною відповідальністю. The article clarifies etymological meaning of «sanction» as the foreign language category. It has been found out that this polysemantic term is interpreted differently, depending on the specific context it is used in: in a general sense there aregrounds to interpret thіs category as approval of the specific decisions and actions by an authorized legal entity. In general, theoretical legal meaning of this concept is often identified with the structural element of the rule of law; in special (sectoral) context this concept acquires the meaning of negative consequences that occur under legal regulations as to the offender of the law or contract. Traditionally, in the general theory of law «sanction» is considered in relation to the institutions of the rule of law (in particular, concerning its structure) and legal responsibility for the offense (the so-called retrospective, negative liability). The majority of the definitions of sanction as a legal norm includes the following important features: 1) it is an element of the rule of law; 2) it is a way to protect the rules of behavior, set forth in the disposition of the legal norms, from its possible violations or in order to prevent their commission; 3) it is an indication to the adverse effects that occur in case of violation of the law; 4) is applied by authorized bodies to bring legal entities to legal responsibility. The concept of positive or prospective responsibility (opposite to legal responsibility for violation of the law) and its instruments – penalties-rewards, sanctions-incentivesare not supported by the author because of its methodological fallacy. The author justifies informational, sociopolitical significance of sanctions in the context of legal norms and tackles it as an expression of condemnation of illegal behavior by the state or society and related to it preventive effect of sanctions. The author supports the relationship and connection of sanctions with legal norms and legal responsibility, which are often wrongly equated by scientists.
Concept of Sanctions in the Theory of Law.
Keywords: норма права; санкція; правопорушення; державний примус; юридична відповідальність; rule of law; sanction; offense; state compulsion; legal liability